Ludwig van Beethoven’s “Fidelio”: Participation of the Public in Graham Vick and Tobias Kratzer’s Productions - Yefimenko, Adelina (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. Versions of the only opus magnum of the German genius in modern filmmaking practice are associated with various sources: from myth, historical documentary to modern political thriller. The performances of Fidelio by the German Tobias Kratzer on the stage of the London Royal Opera and the British Graham Vick with the Birmingham Opera Company directed the vector of directorial innovations into the mainstream of the actual problem in the field of art — communication. Both directors brought the image of an opera audience onto the stage. Main objective of the study is to analyze the aforementioned opera productions from the point of view of the public participation, which presupposes the use of the stage experience of performance, documentary and Immersion Theater. Research methodology. Expending the experience of scientists who have developed the classification of the concepts of the public and the audience, the structural vector of these concepts in the form of a link in the recipient-performer-creator chain is revealed. In the versions from Vick and Kratzer, the public and the audience not only actively influence the artistic processes, but also become their participants. A watershed between the concepts of the public and the audience, important for comparing these artifacts, is revealed which required, provided the reason to use a comparative research methodology. The results of directorial artifacts. Vick interprets “Fidelio” as a performer-director. His fourth interactive version of the opera features Birmingham residents. Kratzer accentuates the historical traditionally theatrical barriers between performers and spectators and first gives the opportunity to relive the events of the costumed “Fidelio”, designed for a suggestive public reaction, which gives impetus to an unexpected evolution. At first, the audience, passively reflecting the events, acquires a certain breakthrough in consciousness in the finale and begins to act on a par with the protagonists of the opera. For Kratzer and Vick, the argument for including the image of the audience in the production was the historical fact (the creation of an opera during the French Revolution) and the coverage of the connections between Beethoven’s opera narrative and the social realities of modern society. Vick associated “Fidelio” with modern outbursts of totalitarianism. For Kratzer, the key idea is ideal love, inherent in Beethoven’s ideas of humanism, loyalty and moral duty. Vick’s Theater connects the type of audience as a spontaneous community. Kratzer focuses on the centuries-old culture of opera lovers united by common interests. The approbation of various forms of integration of performance and opera shows how important the artistic, social, didactic and psychological results of participation are. The public develops, evolves and becomes a professional audience.